2017
DOI: 10.1186/s12878-017-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency blood transfusion practices among anaemic children presenting to an urban emergency department of a tertiary hospital in Tanzania

Abstract: BackgroundSevere anaemia contributes significantly to mortality, especially in children under 5 years of age. Timely blood transfusion is known to improve outcomes. We investigated the magnitude of anaemia and emergency blood transfusion practices amongst children under 5 years presenting to the Emergency Department (ED) of Muhimbili National Hospital (MNH) in Tanzania.MethodsThis prospective observational study enrolled children under 5 years old with anaemia, over a 7-week period in August and September of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
(41 reference statements)
5
21
1
Order By: Relevance
“…In the study hospitals, a diagnosis of ‘severe anemia’ was the indication for blood transfusion in almost all (95%) children that were transfused. Conversely, children not diagnosed with SA were unlikely to be transfused, similar to a Tanzanian study where patients not identified by physicians in the emergency room to have severe anemia were not transfused [ 14 ]. Thus correct diagnosis of severe anemia is a critical step in the appropriate use of blood transfusion in resource limited settings.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the study hospitals, a diagnosis of ‘severe anemia’ was the indication for blood transfusion in almost all (95%) children that were transfused. Conversely, children not diagnosed with SA were unlikely to be transfused, similar to a Tanzanian study where patients not identified by physicians in the emergency room to have severe anemia were not transfused [ 14 ]. Thus correct diagnosis of severe anemia is a critical step in the appropriate use of blood transfusion in resource limited settings.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, giving blood inappropriately not only exposes children to unnecessary risks associated with blood transfusion like transfusion reactions etc. [ 18 ] but also deprives patients who are truly anemic opportunity to get life-saving blood transfusion [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, despite the high proportion of patients with severe anemia, less than half of the patients received transfusion. A previous study carried out at MNH, revealed difficulties in obtaining blood for transfusion, including a general unavailability of blood, scarcity of un-cross matched blood at the blood bank along with delays in obtaining blood [26]. It is worth noting that ED management of UGIB is guided by the presence of departmental protocol for various conditions including UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…In this extensive process they found that mortality from different clinical conditions ( ex: mortality in trauma patients within 24 h of emergency unit (EU) presentation, or transfusion rate among eligible trauma patients presenting to EU) can easily be studied and indicate the quality of care delivery in the EU. In Tanzania, Shari CR et al studied emergency blood transfusion practices among anaemic children presenting to an urban emergency department of a tertiary hospital in which he enrolled under five children who met the world health organization criteria for emergency transfusion [ 25 ]. Forty-nine percent of children with anaemia had indications for blood transfusion, but only 23% were transfused in the EU, and those not transfused had nearly a 3-fold higher mortality.…”
Section: The Components Of a High Quality Emergency Care Systemmentioning
confidence: 99%